The impact of color of artificial LED lighting on microgreen: a review - Envry Artanti Duidahayu Putri; Hauzan Ariq Musyaffa Fajri; Firstina Iswari; Fadlan Atalla Muhammad; Rossita Fauziah; Rahmat Budiarto (Universitas Padjadjaran, 2022)
AbstractMicrogreen is an emerging agricultural food product that its development can be close type system and rely on the presence of artificial lighting, such as LED. Present study aimed to sum up the artificial LED lighting impact on microgreen production. In general, there were three important variables of light for plant, i.e., light intensity, light duration/photoperiod and light quality. The effect of different LED color on microgreen yield and phytochemical content is also revealed in present review. The red, blue, combination of red and blue, green, white, yellow and UV-A light are numerous choice for optimal microgreen production. However, there is no one-to-all recommendation here, since the LED light suitability is depending upon the plant species and target of market.Keywords: artificial lighting, LED color, microgreen, UV-A light AbstrakMicrogreen adalah produk pangan pertanian yang sedang marak dikembangkan dan dapat diproduksi dalam sistem tertutup dengan dukungan pencahayaan buatan seperti LED. Penelitian ini bertujuan untuk mereview dampak penggunaan pencahayaan buatan LED terhadap produksi microgreen. Pada umumnya, terdapat 3 peubah penting cahaya untuk tanaman yakni intensitas cahaya, panjang hari/fotoperiodisitas dan kualitas cahaya. Pengaruh dari perbedaan warna LED terhadap hasil panen dan kandungan fitokimia microgreen dijelaskan pada artikel review ini. Lampu merah, biru, kombinasi merah dan biru, hijau, putih, kuning dan UV-A merupakan berbagai pilihan untuk produksi microgreen yang optimal. Namun tidak ada rekomendasi yang bersifat umum, karena kesesuaian LED bergantung pada faktor jenis tanaman dan target pasar. Kata Kunci: pencahayaan buatan, warna LED, microgreen, lampu UV-A